Development of Nursing Education and Practice in Nigeria - Tanko Titus AUTA (Health Notions, 2019)
Nursing profession is the foremost caring profession that rested, savoured and consolidated on its position through the ages by developing its own language, rituals, arts and sciences from the physical, psycho-social and spiritual needs of the patients. Nigerian nurses face the following challenges that require immediate attention to improve quality services to the citizens; 1) lack of interest in research, 2) work environments, 3) advancement in science and technology, 4) non participation in making policy, 5) nurse herself or himself, 6) quackery, 7) lack of equipment, 8) poor information and ICT system, 9) educational goals and lack of continuous training/re-orientation, 10) the professional association of nurses, 11) governments’ cost saving practice of minimum staff for maximum work which in health care delivery system endangers the health of the citizens as standards and quality are lowered, 12) international organizations and agencies support for health and nursing education and practice development has been dwindling over the years for various political, economic and financial absurdities in governance in Nigeria as well as global economic meltdown in recent years. Keywords: Social capital, Perception, commitment, behavior